The Transspinal Canal Screwing Technique for Atlantoaxial Anomalies: A Technical Note and 2 Case Reports - Kento Takebayashi; Motoo Kubota; Masahito Yuzurihara; Shigekuni Tachibana; Takakazu Kawamata (Neurospine, 2019)
It is difficult to treat atlantoaxial instability in patients with a high-riding vertebral artery or anomalies of the craniocervical junction. We report 2 successful cases in which the transspinal canal screwing technique was used because of difficulties performing conventional fixation methods. Case 1: A 78-year-old woman suffered from progressive myelopathy due to severe spinal cord compression with a congenital anomaly of the craniovertebral junction. Bilateral transspinal canal screws from the axis body with spondylolisthesis to the dens were inserted by retracting the dural sac medially after foramen magnum decompression and cervical laminoplasty. Case 2: A 20-year-old man with a spinal deformity due to Loeys-Dietz syndrome presented to our hospital for treatment of syringomyelia. He had no obvious neurological deficits, but spinal cord compression due to right atlantoaxial rotating dislocation was observed. A screw was inserted from the vertebral body of the axis to the right lateral mass of the atlas via the spinal canal after laminectomy of the atlas. The transspinal canal screwing technique is useful for treating atlantoaxial instability in cases where other fixation methods are difficult.